A Case of Adrenal Myelolipoma Associated with Hereditary Spherocytosis - Dahui Gug; Ha Young Park; Bo Lyun Lee; Kwang Hoon Kim; Jeong Eun Lee; Ji Kyoung Park (The Korean Society of Pediatric Hematology-Oncology, 2021)
Hereditary spherocytosis is the most common hereditary red blood cell membrane disorder. It results from a deficiency in certain proteins that are part of the red blood cell membrane cytoskeleton. We report a case of adrenal myelolipoma in a 23-year-old patient with hereditary spherocytosis. She was diagnosed with hereditary spherocytosis at 7 months of age. As she grew older, hemoglobin level was low, so splenectomy was recommended, but continuous follow up was not possible due to the circumstances of the patient, so the splenectomy was delayed. Adrenal myelolipoma was discovered incidentally at the age of 23 with abdominal pain and cholecystitis with gallstones at the time. Myelolipoma is a benign tumor of the mesenchymal origin; its etiology remains unclear. Myelolipoma is composed of adipose and hematopoietic tissues and mainly arises from adrenal tissues. The mass is often detected during routine radiologic examinations because myelolipoma is usually asymptomatic and not generally associated with hematologic diseases. The prevalence of myelolipoma appears to be increasing due to the increased use of imaging modalities. The association of myelolipoma with hereditary spherocytosis has rarely been reported in the literature. To our best knowledge, this is the first report of adrenal myelolipoma associated with hereditary spherocytosis in the Korean population.